Coronary artery calcium score in predicting periprocedural myocardial infarction in patients undergoing an elective percutaneous coronary intervention. Issue 7 (November 2018) - Kang, Min Gyu; Kang, Yoomee; Jang, Hyun Gyung; Kim, Kyehwan; Koh, Jin-Sin; Park, Jeong Rang; Hwang, Seok-Jae; Hwang, Jin-Yong; Bae, Jae Seok; Ahn, Jong-Hwa; Jang, Jeong Yoon; Park, Yongwhi; et al.
Abstract : Background: This study aimed to evaluate whether the coronary artery calcium score (CACS) measured with computed tomography coronary angiography (CTCA) predicts periprocedural myocardial infarction (PMI) in patients undergoing an elective percutaneous coronary intervention (PCI). Patients and methods: A total of 197 patients with stable angina underwent elective PCI after CTCA. We evaluated CACS using CTCA and assessed the clinical risk factors for PMI. PMI was defined as an elevation of troponin I levels exceeding five times the upper limit of normal within 24 h after PCI. Patients were followed up for major adverse cardiovascular events for a median of 4.6 years. Results: The prevalence of PMI was 18.7% (37 patients) and patients with PMI showed a trend toward a higher CACS (721±779 vs. 498±842, P =0.142). The prevalence of PMI showed a positive correlation with the CACS distribution [8.0%, first interquartile range (IQR); 14.3%, second IQR; 22.4%, third IQR; 30.6%, fourth IQR; P =0.002]. The CACS cut-off value for PMI was greater than 113 (area under the curve: 0.670; 95% confidence interval: 0.600–0.736; P <0.001). Patients with CACS greater than 113 before PCI showed a higher prevalence of PMI (26.2 vs. 5.6%, odds ratio: 5.994; P <0.001). Multivariate analysis showed that CACS greater than 113 was the main predictor for PMI (odds ratio: 3.61, 95% confidence interval: 1.145–11.363; P =0.028). In this study, the cumulative incidence of major adverse cardiovascular event was higher in patients with PMI (54.1 vs. 10.6%; P <0.001). Conclusion: This study suggests that high CACS measured with CTCA influences the occurrence of PMI, which is associated with worse cardiovascular outcomes.